EFFECTS OF IMAGERY ON ACUTE INJURY RECOVERY - Al-kitani, Abdulhameed; Darain, Haider; Ullah, Irfan (Annals of Allied Health Sciences, 2016)
INTRODUCTION: A combination of both physical and psychological intervention is essential during injury recovery and rehabilitation. However, little has been reported in the literature. This study was designed to assess the acutely injured footballer’s beliefs and intention towards the use of psychological interventions of imagery and its types. METHODS: A total of 18 acutely injured male participants volunteered for this trial and introduction to the use of imagery was given to all participants in two government hospitals in the Sultanate of Oman. All participants filled three questionnaires on three different occasions during injury recovery; pre and two post interventions (immediately after and three weeks after intervention). RESULTS: The results showed that imagery’s belief mean immediately after intervention was significantly greater than pre-intervention mean, and that 3 weeks post-intervention mean for imagery intention was significantly greater than the immediately post-intervention mean (dependent t-test). In addition, the results revealed that motivational imagery’s intention had the most significant improvement 3 weeks post intervention than immediately post compared to the other types of imagery (healing imagery and pre-experience). The results of the current study had offered some evidence that imagery is a very useful tool that can be used in the recovery of patients with acute injuries. CONCLUSION: Improved results of beliefs and intention of use of imagery and the use of healing imagery warrant better outcomes in the recovery of acute injuries. Thus, imagery is a very useful tool that can be used for patients suffering acute injuries.